1997
DOI: 10.1038/37648
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative action of interferon-α requires components of T-cell-receptor signalling

Abstract: Signal transduction through both cytokine and lymphocyte antigen receptors shares some common pathways by which they initiate cellular responses, such as activation of mitogen-activated protein kinase(s). However, other signalling components appear to be uniquely coupled to each receptor. For example, the interferon receptors transduce regulatory signals through the JAK/STAT pathway, resulting in an inhibition of growth and of antiviral effects, whereas this pathway apparently plays no role in T-cell-receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
1
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 9 publications
11
96
1
2
Order By: Relevance
“…Our preliminary experiments with anti-phosphotyrosine mAb specific for TEY suggested that short-term PMA stimulation caused phosphorylation of TEY on Jak1 molecules (data not shown). Recently, Petricoin et al (33) reported that the antiproliferative action of IFN-␣ required components of the TCR signaling cascade, such as Lck and ZAP-70. Here, we present evidence that the TCR-mediated Ras͞MAPK activation controls IL-4R-mediated signaling and determines the direction of helper T cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary experiments with anti-phosphotyrosine mAb specific for TEY suggested that short-term PMA stimulation caused phosphorylation of TEY on Jak1 molecules (data not shown). Recently, Petricoin et al (33) reported that the antiproliferative action of IFN-␣ required components of the TCR signaling cascade, such as Lck and ZAP-70. Here, we present evidence that the TCR-mediated Ras͞MAPK activation controls IL-4R-mediated signaling and determines the direction of helper T cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Further in vivo studies will be needed to fully characterize the functional relation between Nras and the immune defense system in the knockout mice. In this regard, it is worth mentioning that the transcriptional data reported here are fully derived from analysis of fibroblasts rather than lymphocytes, and that the available literature indicates that IFN/STAT signaling is mostly independent of T-cell receptor-dependent gene expression or signal-transduction processes (Beadling et al, 1994;Petricoin et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These components were associated with IFNaR1, as judged by co-immunoprecipitation experiments and are essential for signaling via the T-cell receptor (57). Requirement of T-cell receptor signaling components was also reported by other groups, who showed that Stat5, which is constitutively associated with Tyk2, provides upon phosphorylation a docking site for the SH2 domain of CrkL, a protein that is located upstream of the T-cell receptor induced growth-inhibitory C3G/Rap-1 cascade.…”
Section: Discussionmentioning
confidence: 99%